The water crisis and its impact on the future of Iraqi-Turkish relations - Sadiq J. Ali (Journal of Madenat Alelem University College, 2022)
Turkey’s relations with neighboring countries, including Iraq, have created contradictions and reactions that are not easy to overcome. Also, the Turkish location adjacent to Iraq as one of the largest regional countries in terms of land and population, with an expansionist past and ambition for its return, many of its regional and international relations must have direct or indirect repercussions on Iraq's national and national interests.